Precommitment, Cash Transfers, and Timely Arrival for Birth: Evidence from a Randomized Controlled Trial in Nairobi Kenya - Cohen, Jessica; Lofgren, Katherine; McConnell, Margaret (American Economic Review, 2017)
Maternal and neonatal mortality rates in the slums of Nairobi, Kenya are among the highest in the world. Mounting evidence suggests that delivering in a facility is not enough to ensure mortality reductions: women must deliver in high-quality facilities and arrive early enough for appropriate care if complications arise. We designed an RCT combining labeled cash transfers and pre-commitment incentives to encourage earlier and more effective delivery facility choice and to promote earlier facility arrival. We find that the intervention improves planning, increases delivery at the desired facility, and encourages more timely arrival at delivery facilities.